Comprehending and mastering African conflicts the search for sustainable peace and good governance - edited by Adebayo Adedeji (London Zed Books, 1999)
More and more African countries are falling prey to civil war and the disintegration of government authority and social order. Here, for the first time, teams of African scholars based in those countries principally affected examine what is happening. Their findings are only the first step in an ongoing, policy-relevant process of investigation and action. They share a belief that a development agenda designed to improve the lives of the people and strengthen national economies cannot be effectively pursued until the continent masters its problems of governance.
Includes bibliographical references and index.
Keywords: Civil war--Africa, Sub-Saharan--History--20th century